Aspek sumber daya manusia yang menghambat perkembangan perbankan di Indonesia - Putri, Rosyadah Rensy Dwi Murnisa (Maliki Interdisciplinary Journal, 2024)
The emergence of the sharia system in Indonesia was driven by the increasing awareness of the Muslim community regarding the injustice of conventional banking practices. Lack of human resources is one of the factors inhibiting the growth of sharia banking in Indonesia. because many trustworthy and skilled workers join conventional banks, but only a few work in Islamic banks. As a result, human resources in Islamic banks usually lack the capacity to change financial products, understand sharia contracts, and understand and apply sharia banking concepts. Solutions to this problem include developing skilled and qualified human resources in sharia banking institutions, education that provides continuous education to employees and the community as well as holding human resource training in these institutions.